2021
DOI: 10.3390/ijms22041705
|View full text |Cite
|
Sign up to set email alerts
|

ERAP1 and ERAP2 Enzymes: A Protective Shield for RAS against COVID-19?

Abstract: Patients with coronavirus disease 2019 (COVID-19) have a wide variety of clinical outcomes ranging from asymptomatic to severe respiratory syndrome that can progress to life-threatening lung lesions. The identification of prognostic factors can help to improve the risk stratification of patients by promptly defining for each the most effective therapy to resolve the disease. The etiological agent causing COVID-19 is a new coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
(97 reference statements)
0
17
0
Order By: Relevance
“…In the context of SARS-CoV-2, ERAPs have been proposed to play a role [ 43 ] and indeed they were shown to be important for generation of 8-11 amino acid peptides from 15 amino acid precursors [ 44 ]. Additionally, mutations in ERAP2 were shown to be associated with increased risk of death in SARS-CoV-2 infection.…”
Section: Antigen Processingmentioning
confidence: 99%
“…In the context of SARS-CoV-2, ERAPs have been proposed to play a role [ 43 ] and indeed they were shown to be important for generation of 8-11 amino acid peptides from 15 amino acid precursors [ 44 ]. Additionally, mutations in ERAP2 were shown to be associated with increased risk of death in SARS-CoV-2 infection.…”
Section: Antigen Processingmentioning
confidence: 99%
“…Heightened risk of COVID-19 associated mortality is seen in about 27-30% of the population suffering from arterial hypertension, 16.2% of the diabetic population, and 5.8% patients with cardiovascular issues ( Glotov et al, 2021 ). In addition, approximately 60% of the deceased patients are reportedly males ( D’Amico et al, 2021 ). Race and ethnicity appear to have an importance in shaping the course of the COVID-19, as individuals from the black community reportedly contributed to roughly 58 percent of COVID-19 deaths in the United States in 2020 ( Millett et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The observation reported here that it can bind ERAP2 adds a novel piece to the intriguing puzzle regulating the IRAP multifaceted functions, including inflammation. In particular, it has been shown that ACE2 (Angiotensin I-converting enzyme-2) is the receptor for SARS-COV-2 (45) and it has been postulated that its reduction in the cell membrane due to the endocytic pathway associated with SARS-CoV-2 binding, can play a role in altering the inflammatory balance (16). ERAP2 "short" 20 fragment secreted by type 2 macrophages, by binding IRAP is likely to interfere with the RAS (Renin-Angiotensin-System) by modulating its anti-inflammatory arm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the three genes have been found associated with autoimmune and inflammatory conditions, hypertension, and cancer (2,(9)(10)(11)(12)(13)(14)(15). Since they are regulators of the Renin-Angiotensin system (RAS), their imbalance can have indeed consequences on different aspects of the associated pathologies (16)(17)(18). In the MHC-I-opathies (19), while ERAP1 association resides in variants influencing its trimming activity, the molecular terms of the association of ERAP2 and LNPEP with some of these diseases are at present poorly understood (20).…”
Section: Introductionmentioning
confidence: 99%